Critical Checklist of the Indian species of Hypogastrura (Collembola: Hypogastruridae) with a description of a new species from Satkosia Wild Life Sanctuary - Mandal, Guru Pada; Arbea, Javier (Zootaxa, 2019)
Ten Hypogastrura species have been found from India, two of which are described: H. unguiculata (Mitra, 1966) and H. satkosiaensis nov. sp. Two Indian species have been removed from Hypogastrura and have been included in the genus Ceratophysella based on their original descriptions: C. baltica (Tyagi & Baijal, 1982) comb. nov. and C. katraensis (Tyagi & Baijal, 1982) comb. nov. H. satkosiaensis sp. nov. belongs to H. manubrialis group of species within the genus and is easily separated from the other members of the group by a combination of characters, a greater number of antennal sensilla, dorsal chaetotaxy, specially presence of m1 chaeta on abdominal tergite V, and mucro shape. A key for all of the known Indian species of Hypogastrura is provided.